Reconfiguring Memory. Adaptive Reuse of Barranco's Historical Heritage in the 21st Century - Fernández Checa, Daniela (2024)
The definition of part of Lima’s district, Barranco, as a Monumental Zone towards the end of the nineties displayed the precarious state of the properties valued as cultural assets. Thus, in the search for the perdurance of the heritage and continuous use of these assets, adaptive reuse interventions arise in the 21st century, in the district.This research proposes architectural recycling as a viable intervention for the conservation and longevity of the built heritage. Therefore, initiating from the understanding of these structures as the integrity of their history and different stages of their intervention, physical changes are analyzed as a representation of their design strategies and their spatial results in three case studies. These, considered valuable examples to signify the above-mentioned viability of adaptive reuse in other monumental areas.